2021
DOI: 10.2147/ijgm.s337769
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD5L and SRD5A2 as Prognostic Biomarkers for Hepatocellular Carcinoma

Abstract: Due to the limitations of currently available biomarkers, new biomarkers are needed to accurately predict the prognosis of patients with hepatocellular carcinoma (HCC) patients. Methods: In this study, we screened for differentially expressed genes (DEGs) in the tumor and the adjacent tissues using the four gene expression array (GSE14520, GSE45267, GSE121248, GSE62232) of the Gene Express Omnibus (GEO) database. Results: Subsequently, 47 overlapping DEGs were identified in four GEO datasets, which were mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…CD5L presented with abnormal mRNA and protein levels in HCC and it was found to be an independent prognostic factor for HCC patients. [63,64] DAB2 promotes epithelial-mesenchymal transition and invasion of tumor cells at advanced tumor stages, and it acts as a risk factor in HCC, [65] which is consistent with our findings. High expression of IMPDH1 is associated with poor prognosis of HCC patients and may serve as a potential target for immunotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…CD5L presented with abnormal mRNA and protein levels in HCC and it was found to be an independent prognostic factor for HCC patients. [63,64] DAB2 promotes epithelial-mesenchymal transition and invasion of tumor cells at advanced tumor stages, and it acts as a risk factor in HCC, [65] which is consistent with our findings. High expression of IMPDH1 is associated with poor prognosis of HCC patients and may serve as a potential target for immunotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the LIHC patients with high-CD5L mRNA levels showed a favorable prognosis. Consistently, Luo et al 's [ 21 ] study also showed that CD5L can be an independent favorable prognostic factor for LIHC patients. Interestingly, our analysis further showed that there was no significant prognostic value of CD5L mRNA expression in LIHC patients with hepatitis virus infection.…”
Section: Discussionsupporting
confidence: 60%